The Chinese aesthetic tradition - Li, Zehou; Samei, Maija Bell, 1965- (Honolulu : University of Hawaiʻi Press, 2010)
Touching on all aspects of artistic activity, Li demonstrates the fundamental role of aesthetics in the development of the cultural & psychological structures in Chinese culture that define 'humanity'.
The rites and music tradition -- Confucian humanism -- The Daoist-Confucian synthesis -- Beauty in deep emotion -- Metaphysical pursuits -- Toward modernity.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Aesthetics, Chinese -- History; Esthétique chinoise -- Histoire; PHILOSOPHY -- Aesthetics; PHILOSOPHY -- Eastern; Aesthetics, Chinese; Ästhetik; China; Geschichte; Electronic books; History